Processo rápido para descascamento de manga - Marcondes Borges, José; Pinto, Geraldo Luiz; de Paula Pereira, Vicente (Revista Ceres, 2025)
Experiments were recently conducted in the Food Tchnology Department of the Federal University of Viçosa in order to find a more efficient alternative to the present industrial process used for peeling mangoes. This is a manual process which utilizes special knives and although it is a slow and expensive technique, it is the only one presently being used.